Facile Controlled Synthesis of Spinel LiMn2O4 Porous Microspheres as Cathode Material for Lithium Ion Batteries - Hai, Yun; Zhang, Ziwei; Liu, Hao; Liao, Libing; Fan, Peng; Wu, Yuanyuan; Lv, Guocheng; Mei, Lefu (Frontiers in Chemistry, 2019)
Although the electrochemical properties of porous LiMn2O4 microspheres are usually improved as compared to those of irregular LiMn2O4 particles, the effects of the different synthesis conditions on the preparation of the porous LiMn2O4 microspheres are rarely discussed in detail. In present work, porous LiMn2O4 microspheres had been successfully synthesized by using molten LiOH and porous Mn2O3 spheres as a template. Multiple factors were considered in the preparation process, including reagent concentration, pH, adding mode, annealing time etc. The morphology of MnCO3 template was crucial for the preparation of porous LiMn2O4 microspheres and it was mainly affected by the concentration of reactants and pH value of the solution during the precipitation process. During the lithiation of Mn2O3 microspheres, the annealing temperature and the ratio between Mn2O3 and lithium salt were the most significant variables in terms of control over the morphology and purity of the LiMn2O4 microspheres. Furthermore, we demonstrated that the porous LiMn2O4 microspheres presented better rate capability and cyclability as compared to commercial LiMn2O4 powder as cathode materials for lithium-ion batteries. This study not only highlighted the shape controllable synthesis of LiMn2O4 microspheres as promising cathode materials, but also provided some useful guidance for the synthesis of porous LiMn2O4 microspheres or other LIB’s electrode materials.